The Relationship between Nutritional Status and Fundamental Movement Skills of Elementary School Students - Rifky Ihsan Purnama; Lukmannul Haqim Lubay; Wulandari Putri (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The nutritional status and fundamental movement skills are one of things that are quite important for the growth and development of children. The nutritional status of children can affect a person's movement skills and fundamental basic movements can be related to daily activities. This research was conducted to know the relationship between nutritional status and fundamental movements in elementary schools. This type of research is a correlational study with a non-experimental research design. Participants included were grade IV students with an age range of 10-11 years of 100 people. The instruments used were BMI measurements and the TGMD-2 test. Data analysis techniques using formulas in the SPSS with spearman correlation. The results showed that the sig value of BMI and basic movement was 0.799 > 0.05 with a correlation coefficient value of 0.26. From these results, it can be concluded that there is no significant relationship between nutritional status and fundamental movement skills in elementary schools.